Hubungan Pengetahuan dan Sikap Ibu Dengan Pemakaian Alat Kontrasepsi Implant di Puskesmas Kedai Sianam Tahun 2022 - Afrida Yelni (Pusat riset dan Inovasi Nasional, 2022)
Family planning is an attempt by a married couple to regulate the number and distance of children desired. The effort in question is contraception or prevention of pregnancy and family planning, the basic principle of contraceptive methods is to prevent male sperm from reaching and fertilizing a woman's egg. This study aims to determine the relationship between knowledge and attitudes of mothers with the use of implantable contraceptives at the Kedai Sianam Health Center in 2022. This research is an analytical research with a cross-sectional study design. The population in this study was all mothers who used contraceptive implants at the Kedai Sianam Health Center as many as 157 people. Samples were obtained as many as 61 people. Data analysis using univariate and bivariate analysis with Chi Square test. The results showed that there was a relationship between maternal knowledge and the use of implantable contraceptives (p = 0.008). There is an attitudinal relationship with the use of implantable contraceptives (p = 0.000). Thus, it is recommended that mothers take the time to attend counseling organized by health workers at Puskesmas about family planning services so as to increase knowledge, attitudes of mothers about implanted contraceptives.